Standardized measurement of breathlessness during exercise. Issue 3 (September 2019) - Lewthwaite, Hayley; Koch, Emily M.; Tracey, Lauren; Jensen, Dennis
Abstract : Purpose of review: Exertional breathlessness is common and pervasive across various chronic disease populations. To accurately assess response to intervention and optimize clinical (symptom) management, detailed assessment of exertional breathlessness is imperative. This review provides an update on current approaches to assess exertional breathlessness and presents the need for individualized assessment of breathlessness standardized for the level of exertion. Recent findings: Breathlessness assessment tools commonly invite people to recall their breathlessness while at rest with reference to activities of daily living. To directly quantify breathlessness, however, requires assessment of the dimensions of breathlessness (e.g., sensory intensity, quality, and unpleasantness) in response to a standardized exercise stimulus. Different exercise stimuli (e.g., self-paced, incremental, and constant work rate exercise tests) have been used to elicit a breathlessness response. Self-paced (e.g., 6-min walk test) and incremental exercise tests assess exercise tolerance or endurance, and are not recommended for assessment of exertional breathlessness. Constant work rate tests, however, including recently validated 3-min constant-rate stair stepping and walking tests, standardize the exercise stimulus to enable the breathlessness response to be directly quantified and monitored over time. Summary: To adequately guide symptom management and assess intervention efficacy, clinicians and researchers should assess breathlessness with multidimensional assessment tools in response to a standardized and individualized exercise stimulus.